Ayurvedic Management of Alzheimer’s Dementia with Depressive Symptoms - A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
Dementia is a syndrome due to degeneration of the cerebral cortex, usually of a chronic or progressive nature, in which there is disturbance of multiple higher cortical functions, including memory, thinking, orientation, calculation, comprehension, capacity to learn, language skills and judgment. Alzheimer’s dementia, Frontotemporal dementia, dementia with lewy bodies, vascular dementia, Huntington’s dementia and Parkinson dementia are the types of dementia. Alzheimer’s dementia is the most common one among the category. The prevalence of depressive symptoms in dementia is 30% and is presented with symptoms such as poor appetite, sleep perversions and social withdrawal. Features of Smrti vibhrama and characteristics of Pranavrta vyana are being observed Alzheimer’s dementia. There is still no effective cure for dementia in contemporary medicine. So, developing an Ayurvedic protocol to treat dementia is a necessity. This is the case of a 72-year-old male presented with loss of interest in daily activities, fatigue, reduced appetite and increased sleep for duration of 7 months and underwent treatment for 1 month. Diagnosis was done based on the criteria in DSM 5 and the severity was assessed by Mini- mental status Examination and Hamilton’s Depression Scale. The management was a combination of modalities including Deepana, Pacana, Virecana, Nasya and follow-up of 1 month. The treatment modalities were found to be effective in the cognitive and depressive symptoms as well as improving the social behaviour in dementia patient.